2016
DOI: 10.1519/jsc.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

GPS and Injury Prevention in Professional Soccer

Abstract: This study investigated the relationship between GPS variables measured in training and gameplay and injury occurrences in professional soccer. Nineteen professional soccer players competing in the Australian Hyundai A-League were monitored for 1 entire season using 5 Hz Global Positioning System (GPS) units (SPI-Pro GPSports) in training sessions and preseason games. The measurements obtained were total distance, high-intensity running distance, very-high-intensity running distance, new body load, and meters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
4
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 34 publications
4
146
4
13
Order By: Relevance
“…Other specific measurement types identified by teams included rating of perceived exertion (RPE) heart rate (HR) and GPS. Although not currently shown in elite football players, workloads from training and matches as measured using RPE17–21 were associated with injury in other elite team sports, while early, albeit limited, studies in elite footballers have shown a link between injury and workload as measured using HR22 and GPS 23. Until research further validates (or refutes) these workload variables in professional football, the current limited and, in some cases, extrapolated evidence may provide an insight into how elite football teams might be able to interpret their workload data as calculated from RPE, HR and GPS; specifically, these aforementioned studies have shown that high cumulated loads and acute spikes/increases in load for players may provide pertinent information.…”
Section: Discussionmentioning
confidence: 93%
“…Other specific measurement types identified by teams included rating of perceived exertion (RPE) heart rate (HR) and GPS. Although not currently shown in elite football players, workloads from training and matches as measured using RPE17–21 were associated with injury in other elite team sports, while early, albeit limited, studies in elite footballers have shown a link between injury and workload as measured using HR22 and GPS 23. Until research further validates (or refutes) these workload variables in professional football, the current limited and, in some cases, extrapolated evidence may provide an insight into how elite football teams might be able to interpret their workload data as calculated from RPE, HR and GPS; specifically, these aforementioned studies have shown that high cumulated loads and acute spikes/increases in load for players may provide pertinent information.…”
Section: Discussionmentioning
confidence: 93%
“…In football, some athletes have a relative under-loading of external loads prior to injury,25 as can be observed in fringe and non-selected players accumulating lower training volumes across a season 26. Equally, in cricket, fast bowlers who have an ACWR <0.50 display increased risk of injury compared to those with a higher ratio (ACWR, 0.5–0.99) 22…”
Section: Prevention Based On Risk Factors For Developing a Sports Injurymentioning
confidence: 99%
“…It has also been suggested that high chronic loads give athletes the opportunity to develop physical qualities that could potentially have a preventive effect [95]. In football, associations between relative load and injuries have been observed in a study in which low and high relative load (depending on which method was used when measuring load) compared with players' season average was shown to be associated with an increased risk of injury [96]. One way of defining relative load is the acute to chronic workload ratio [95].…”
Section: Load and Injuries In The Football Codesmentioning
confidence: 99%